Association of Ankle Arthritis Score With Need for Revision Surgery. (September 2017) - Croft, Stephen; Wing, Kevin J.; Daniels, Timothy R.; Glazebrook, Mark; Dryden, Peter; Younger, Alastair; Penner, Murray J.; Sutherland, Jason M.
Background: The Ankle Arthritis Score (AAS) is a new patient-reported outcome derived from the Ankle Osteoarthritis Scale (AOS). This study analyzed longitudinally collected data from a cohort of patients in the Canadian Orthopaedic Foot and Ankle Society (COFAS) Ankle Arthritis Study in order to evaluate whether the postoperative AAS is associated with need for revision surgery. Methods: A multicenter, prospective, ankle-reconstruction study enrolled 653 ankles undergoing total ankle replacement (TAR) or ankle arthrodesis (AA). The AAS was given at baseline and annually during postoperative follow-up. Time to revision surgery was modeled using a proportional hazards model. The final sample included 531 ankles in 509 patients. Results: Sixty-two patients underwent metal-component revision and 8 underwent arthrodesis revision during the follow-up time period. The remaining 461 unrevised ankles (300 TAR, 161 AA) had a minimum follow-up of 2 years (average of 3.4 years). Revision surgery after TAR was found to be associated with a higher postoperative AAS and a longer follow-up. The hazard ratio for the AAS indicated that for every 1-point increase in the score, the rate of revision surgery after TAR was 1 percentage point higher. Conclusions: TAR patients who reported higher levels of postoperative functional impairment, as indicated by a higher AAS, were more likely to require metal-component revision surgery. After adjustment for other patient factors, the risk of revision surgery increased with length of follow-up after TAR. This study provides further evidence for the utility of the AAS in the clinical setting. Level of Evidence: Level III, retrospective cohort study.